Determinants of millet diversity at the household-farm and village-community levels in the drylands of India: The role of local seed systems - Nagarajan, Latha; Smale, Melinda; Glewwe, Paul (Wiley, 2007)
This research characterizes the biological diversity of millet crops in the semiarid regions of India at the household and village‐community ( panchayat) scales of analysis, placing that evidence in the context of local seed systems. A set of seed system parameters that span formal and informal exchange and can be measured empirically are proposed. The analysis is based on data collected through sample surveys of farmers and traders in selected sites of Karnataka and Andhra Pradesh, combined with cultivar taxonomies developed with geneticists and applied to seed samples. Findings demonstrate that millet crop diversity levels at both scales of analysis are significantly influenced by seed system parameters, factors which related studies have omitted. In particular, the presence of active local (formal and informal) seed markets enhances millet richness among and within farming communities. Crop improvement strategies oriented toward local seed markets could provide important benefits and incentives to farm households living in these marginal environments. There is a need, however, for an enhanced theoretical understanding of local seed markets in analyzing crop variety choices and the diversity of materials grown in less favored environments.